Amphibia, Anura, Hylidae, Argenteohyla siemersi pederseni (Williams and Bosso, 1994): first record and some hematological data in Santa Fe Province, Argentina - Lajmanovich, Rafael Carlos (2012)
We herein report on the first west-southern most record of Argenteohyla siemersi pederseni in Argentina. Thisfinding was recorded ca. 250 km far from the nearest known locality in Corrientes, and also enlarges the distribution rangefor including for the Santa Fe Province.